Comparison of contemporary preoperative risk models at predicting acute kidney injury after isolated coronary artery bypass grafting: a retrospective cohort study. Issue 6 (27th June 2016) - Chen, Shao-Wei; Chang, Chih-Hsiang; Fan, Pei-Chun; Chen, Yung-Chang; Chu, Pao-Hsien; Chen, Tien-Hsing; Wu, Victor Chien-Chia; Chang, Su-Wei; Lin, Pyng-Jing; Tsai, Feng-Chun
Abstract : Objectives: Acute kidney injury (AKI) after coronary artery bypass grafting (CABG) is associated with short-term and long-term adverse outcomes. The European System for Cardiac Operative Risk Evaluation (EuroSCORE), EuroSCORE II, the Society of Thoracic Surgeons (STS) score and Age, Creatinine and Ejection Fraction (ACEF) score, have been widely used for predicting the operative risk of cardiac surgery. The aim of this study is to investigate the discriminant ability among current available models in predicting postoperative AKI. Methods: From January 2010 to December 2012, 353 patients who underwent isolated CABG were enrolled. The clinical characteristics, outcomes and scores of prognostic models were collected. The primary outcome was postoperative AKI, defined based on the Kidney Disease Improving Global Outcome (KDIGO) Clinical Practice Guideline for AKI, in 2012. Results: 102 patients (28.9%) developed postoperative AKI. For AKI prediction, EuroSCORE II, STS score and ACEF score were all good tools for stage-3 AKI. The ACEF score was shown to have satisfied discriminant ability to predict postoperative AKI with area under a receiver operating characteristic curve: 0.781±0.027, (95% CI 0.729 to 0.834, p value <0.001). Multivariate logistic analysis identified that lower ejection fraction and higher serum creatinine were independent risk factors for AKI. Conclusions: The simple and extremely user-friendly ACEF score can accurately identify the risk of postoperative AKI and has shown satisfactory discriminant ability when compared with other systems. The ACEF score might be the easiest tool for predicting postoperative AKI.